Phylogenetic Analysis of Sulawesi Endemic Butterfly Papilio polytes Using the COI (Cytochrome Oxidase I) Gene - Andi Nurjannah; Lestari MP Alibasyah; Manap Trianto; Masrianih Masrianih; Yulia Windarsih; Amalia Buntu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Papilio polytes is a butterfly belonging to the family Papilionidae and is endemic to Sulawesi. The evolutionary relationships of this species were investigated through phylogenetic analysis based on mitochondrial DNA, specifically the COI (Cytochrome Oxidase I) region, which was subsequently reconstructed into a phylogenetic tree. This study aimed to analyze the phylogenetic relationships of P. polytes collected from Bakubakulu Village, Palolo District, Sigi Regency, Central Sulawesi, in relation to other members of the genus Papilio from different regions. Specimens of P. polytes were collected using a roaming (exploratory) method, followed by DNA isolation, DNA amplification, sequencing, electrophoresis, and bioinformatics analyses using GeneStudio, DNASTAR, MESQUITE, and MEGA 11. The phylogenetic tree analyses using the Neighbor Joining (NJ) and Maximum Likelihood (ML) methods revealed clear evolutionary relationships. Papilio polytes from Central Sulawesi showed a closer genetic relationship with P. polytes from other regions and clustered within the same clade, whereas other species formed separate clades. Genetic distance analysis based on the COI gene indicated that P. polytes from Central Sulawesi exhibited a genetic distance of 0.00% among individuals, suggesting very high genetic similarity within the population. The genetic distance between P. polytes from Central Sulawesi and P. polytes populations from other regions was relatively low, ranging from 0.00% to 3.86%, while the distance to the outgroup species Eurytides marcellus and Battus polydamas was much higher, ranging from 13.15% to 16.25%. These findings indicate that the phylogenetic relationships among P. polytes populations are very close and consistent.